2022
DOI: 10.3390/ijms232213823
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin (mTOR) Signaling at the Crossroad of Muscle Fiber Fate in Sarcopenia

Abstract: The mammalian target of rapamycin (mTOR) is a major regulator of skeletal myocyte viability. The signaling pathways triggered by mTOR vary according to the type of endogenous and exogenous factors (e.g., redox balance, nutrient availability, physical activity) as well as organismal age. Here, we provide an overview of mTOR signaling in skeletal muscle, with a special focus on the role played by mTOR in the development of sarcopenia. Intervention strategies targeting mTOR in sarcopenia (e.g., supplementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 103 publications
(137 reference statements)
0
9
0
Order By: Relevance
“…Many downstream pathways and factors relating to muscle regeneration may be regulated and activated by mitochondria, including the mammalian target of rapamycin complex 1 (mTORC1), Kelch-like ECH-associated protein 1 (KEAP1), and NF-E2-related factor 2 (NRF2) ( Rai and Dey, 2020 ). The mammalian target of rapamycin (mTOR) has been proven to be the key regulator of muscle regeneration and to regulate bone metabolism by stimulating protein synthesis and inhibiting proteolysis ( Sirago et al, 2022 ). Inflammaging, a chronic inflammatory phenomenon occurring in older individuals and characterized by an increase in proinflammatory cytokines and a decrease in anti-inflammatory cytokine levels, was also a cause of many geriatric syndromes, including sarcopenia ( Bencivenga et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many downstream pathways and factors relating to muscle regeneration may be regulated and activated by mitochondria, including the mammalian target of rapamycin complex 1 (mTORC1), Kelch-like ECH-associated protein 1 (KEAP1), and NF-E2-related factor 2 (NRF2) ( Rai and Dey, 2020 ). The mammalian target of rapamycin (mTOR) has been proven to be the key regulator of muscle regeneration and to regulate bone metabolism by stimulating protein synthesis and inhibiting proteolysis ( Sirago et al, 2022 ). Inflammaging, a chronic inflammatory phenomenon occurring in older individuals and characterized by an increase in proinflammatory cytokines and a decrease in anti-inflammatory cytokine levels, was also a cause of many geriatric syndromes, including sarcopenia ( Bencivenga et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies emphasize that calcineurin and mTOR inhibitors, which are other immunosuppressive agents used in patients, also cause muscle atrophy since it disrupts protein metabolism. The mTOR pathway, which has an anabolic effect on muscle protein metabolism and skeletal muscles, plays an essential role in cell growth 27 . Yoshino et al showed that when Omega‐3 polyunsaturated fatty acids were added to the diet, the inhibition of the mTOR pathway decreased, which had positive results in skeletal muscle production 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The mTOR pathway, which has an anabolic effect on muscle protein metabolism and skeletal muscles, plays an essential role in cell growth. 27 Yoshino et al showed that when Omega-3 polyunsaturated fatty acids were added to the diet, the inhibition of the mTOR pathway decreased, which had positive results in skeletal muscle production. 28 Calcineurin inhibitors (e.g., cyclosporine, tacrolimus, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…mTOR is another major regulator of myocyte homeostasis [13]. Hyperactivation of mTOR during aging has a negative impact on muscle protein synthesis and favors muscle loss [87].…”
Section: Mitochondria and Muscle Agingmentioning
confidence: 99%
“…Additional systems have been implicated in the regulation of muscle plasticity and trophism such as the tightly modulated and complex interplay between the stimulator of protein synthesis, mechanistic target of rapamycin (mTOR), and the inhibitor of mTOR, AMP-activated protein kinase (AMPK), that promotes muscle catabolism [13].…”
Section: Introductionmentioning
confidence: 99%